PENATAAN MEKANISME SELEKSI PENGANGKATAN HAKIM DI LINGKUP KEKUASAAN MAHKAMAH AGUNG DIKAITKAN DENGAN INDEPENDENSI KEKUASAAN KEHAKIMAN - Try Fauzan Permana; Emilda Firdaus; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Judge appointment selection is actually intended that can generate th best judge, could keep the judge dignity and has integrity in works. But, since the constitutional court decision Number 43/PUU-XII/2015 has released, the people and legal advicer doubt with credibility and integrity of judge who is generated through judge appointment selection which is just involving supreme court, included the author. The purpose of this paper is not just to describe the urgency of the involvement of yudicial commission in the process of judge appointment selection, but the author want to give the new scheme of judge appointment selection which is involving the people because today, the judge is public office.The type of this research can be classified in the type of normative law research is literature. In this normative law research, the author make the research against principles of law. The conclution of this research is the judicial commission must be involved in judge appointment selection to maintain the dignity and integrity of judge and generate the qualified judge, because the regulatory process has did early and could maintain the independence of judicative power. Then, in this research is also concluding that is not just involve judicial commission and supreme court, but also involve people so that is form a new scheme which can generate the qualified judge.